2019
DOI: 10.1016/j.gpb.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

PsyMuKB: An Integrative De Novo Variant Knowledge Base for Developmental Disorders

Abstract: De novo variants (DNVs) are one of the most significant contributors to severe early-onset genetic disorders such as autism spectrum disorder, intellectual disability, and other developmental and neuropsychiatric (DNP) disorders. Presently, a plethora of DNVs have been identified using next-generation sequencing, and many efforts have been made to understand their impact at the gene level. However, there has been little exploration of the effects at the isoform level. The brain contains a high level of alterna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…We focused on genes harboring mutations and differentially expressed genes in SCZ patients’ brains to define the subsets of different kinds of functional genes in SCZ. We first collected genes with genetic variants (MUTs), including CNVs and the DNMs of SCZ from PsyMuKB [ 16 ], as well as 2363 and 2981 genes that were identified to be differentially expressed between an adult with schizophrenia and a healthy control in DLPFC and HIPPO, respectively, with p.adj <0.05 and fold changes >1.2. Next, we extracted the AB gene set from PsyMuKB [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We focused on genes harboring mutations and differentially expressed genes in SCZ patients’ brains to define the subsets of different kinds of functional genes in SCZ. We first collected genes with genetic variants (MUTs), including CNVs and the DNMs of SCZ from PsyMuKB [ 16 ], as well as 2363 and 2981 genes that were identified to be differentially expressed between an adult with schizophrenia and a healthy control in DLPFC and HIPPO, respectively, with p.adj <0.05 and fold changes >1.2. Next, we extracted the AB gene set from PsyMuKB [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…We first collected genes with genetic variants (MUTs), including CNVs and the DNMs of SCZ from PsyMuKB [ 16 ], as well as 2363 and 2981 genes that were identified to be differentially expressed between an adult with schizophrenia and a healthy control in DLPFC and HIPPO, respectively, with p.adj <0.05 and fold changes >1.2. Next, we extracted the AB gene set from PsyMuKB [ 16 ]. We observed a significant overlap between the AB gene set and the DNM gene (p.adj = 4.04 × 10 −38 calculated using a hypergeometric test and adjusted with a Bonferroni test) but no significant overlap between the AB gene set and the CNV gene (p.adj = 0.138 calculated by a hypergeometric test and adjusted by a Bonferroni test) ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease results from distal deletions on the short arm of chromosome 4 (chromosome 4p16.3) ( Descartes et al, 2017 ), which occurs in 1 in 50,000 births ( Deardorff and Zackai, 2007 ). NSD2 carries rare mutations in patients with neuropsychiatric disorders, including autism spectrum disorder (ASD), DDs, IDs, and schizophrenia (SCZ; Boczek et al, 2018 ; Park et al, 2018 ; Barrie et al, 2019 ; Lin et al, 2019 ). Early studies have reported various deleterious NSD2 variants in neuropsychiatric patients, suggesting that the haploinsufficiency of NSD2 might be partially responsible for DDs ( Katoh, 2016 ; Kim et al, 2017 ; Derar et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%